The Vaccination Cold War. Issue 5 (16th September 2021) - Moreno, Jonathan D.; Sándor, Judit; Schmidt, Ulf
Abstract: Surveying the early responses to the Covid‐19 pandemic among nation states, one finds a veritable babel of responses, some predictable and some not. Would these results have been different half a century or more ago, when smallpox was eradicated and hopes were high that international cooperation would yield similar results for other infectious diseases? Is this a story about the stability provided by the bipolar postwar world, juxtaposed with the complex geopolitical repositioning that finally followed the collapse of the Soviet Union, or is that too rich an irony? A multipolar world may indeed be less prepared to cope with an international health crisis than a bipolar one. In any case, the patterns of global response are not only reminiscent of the Cold War era itself but also suggestive of a new vaccination cold war .